Pharmacokinetic Study of 7 Compounds Following Oral Administration of Fructus Aurantii to Depressive Rats - Zhang, Xianhua; Han, Linran; Liu, Jin; Xu, Qiuyue; Guo, Yuxin; Zheng, Wan; Wang, Jian; Huang, Xi; Ren, Ping (Frontiers in Pharmacology, 2018)
In the present study, the pharmacokinetics of multi-components (naringenin, nobiletin, meranzin hydrate, narirutin, naringin, hesperidin and neohesperidin) were investigated in acute depressive rats following oral administration of Fructus Aurantii (Zhi-Qiao, ZQ) extract (20 g/kg). A sensitive and selective liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed to quantitatively or qualitatively analyze the 7 absorbed ingredients in the plasma, hippocampus and cortex of acute depressive rats. Biological samples were separated on a 300SB-C18 column, and the 7 compounds were detected with sequential positive and negative ionization modes. Our results confirmed that ZQ has antidepressant effects by decreasing the immobility time. In addition, this validated method showed good linearity (r ≥ 0.9987), and the lower limits of quantification were 2.73-16.38 ng/mL for the 7 analytes. This method successfully determined the pharmacokinetics of the 7 compounds and separated two pairs of isomers in plasma of acute depressive rats following oral administration of ZQ extracts. The 7 active ingredients were also identified as marked compounds in target tissues and should be further examined in pharmacokinetic studies with acute depressive rats. So, pharmacokinetic compounds were precisely linked with the antidepressant effect of ZQ in our study. This relationship is well-understood and contributes to the application of Traditional Chinese Medicine (TCM).